Comprehensive technical analysis of a kickboxing fight in K1 format based on observation - Marta NIEWCZAS; Wojciech WĄSACZ; Wiesław CHWAŁA; Tomasz PAŁKA; Ewa SOBIŁO-RYDZIK; Tadeusz AMBROŻY; Kristína NĚMÁ; Łukasz RYDZIK (Baltic Journal of Health and Physical Activity)
Introduction: Observation and specialized analysis of confrontations in combat sports are fundamental for introducing corrections in training programs and for modifying the individual technical-tactical profiles of athletes in these types of activities. These actions comprehensively assess the progress of sports activities, ultimately inspiring and guiding the direction of training in sports clubs. The aim of this study was to analyze and assess the level of the offensive structure of Kickboxing sport fights in the K1 format, in terms of global simulated sparring, in selected thematic sets. Materials and Methods: The research material consisted of a multimedia recording of 10 simulated K1 sparring sessions, in which 20 professional athletes of this discipline participated (age: 24.5 ± 4.6 years; body height: 179.1 ± 4.6 cm; body weight: 81.7 ± 9.9 kg; BMI: 25.5 ± 3.7; training experience: 6.9 ± 1.3 years). To assess the offensive structure of the fight, a retrospective analysis of the recorded empirical material was conducted in terms of the quantity of attacks made, and then specialized technical-tactical preparation (PTT) indicators were calculated, in the global context of sparring, for thematic sets (total; punches vs kicks; right vs left limb attacks; type of techniques; direction of attack). Results: The analysis revealed a significantly higher technical-tactical efficiency regarding hand strikes, left hand, and direction of strikes to the opponent's head in terms of activity (p < 0.001), effectiveness (p < 0.001), and efficiency (p = 0.008–0.408) of attack. In isolated analysis of kicking techniques, a significant advantage in efficiency was registered for selected attacks directed at the lower parts of the opponent's body, i.e., torso, legs (p =< 0.001–0.043). The most effective and exploited techniques were: left straight (Aa x̃=36.8; Sa x̃=23.9), and for kicks, right low kick (Aa x̃=14.9; Sa x̃=5.6). The highest attack efficiency was noted for the right middle kick (Ea x̃=54.18). Several selected comparative sets (inter-limb symmetry, type of attack, direction of attack) for technical-tactical efficiency, were characterized by significant statistical differentiation (p=<0.001–0.048). Conclusions: Kickboxing is an asymmetrical combat sport, which necessitates the application of targeted training on individual body segments of the athlete, and compensatory actions in the prevention of injuries. The study results allow for detailed diagnosis and interpretation of the technical-tactical profile along with the key manifestation of offensive competencies in Kickboxing profession in the K1 format, favoring the optimization of the quality of coaching control.